2020
DOI: 10.1177/2040622320964125
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in therapeutic drugs targeting of senescence

Abstract: Aging leads to a high burden on society, both medically and economically. Cellular senescence plays an essential role in the initiation of aging and age-related diseases. Recent studies have highlighted the therapeutic value of senescent cell deletion in natural aging and many age-related disorders. However, the therapeutic strategies for manipulating cellular senescence are still at an early stage of development. Among these strategies, therapeutic drugs that target cellular senescence are arguably the most h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 197 publications
(245 reference statements)
0
38
0
Order By: Relevance
“…Dendritic arborization, length, synapse number, and spine density decrease to variable degrees in cortical areas. This is accompanied by reductions in most aspects of cognitive performance including memory, awareness, and intellectual abilities (Zhu et al, 2020 ). It can be speculated that brain aging, similarly to that of other organs, is caused by senescent cells.…”
Section: Senolytics In Brain Rejuvenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendritic arborization, length, synapse number, and spine density decrease to variable degrees in cortical areas. This is accompanied by reductions in most aspects of cognitive performance including memory, awareness, and intellectual abilities (Zhu et al, 2020 ). It can be speculated that brain aging, similarly to that of other organs, is caused by senescent cells.…”
Section: Senolytics In Brain Rejuvenationmentioning
confidence: 99%
“…The senolytic treatment, without genetic manipulations, has already been applied in many mouse models of age-related disease ( Figure 5B ). In general, senolytics can be classified into BCL family inhibitors, PI3K/AKT inhibitors, and FOXO regulators (Zhu et al, 2020 ). Briefly, the BCL family is composed of anti-apoptotic and pro-survival proteins, including BCL-2 and BCL-xL, the selective inhibition of which has been previously shown to cause cell death in some cancers (e.g., Souers et al, 2013 ).…”
Section: Senolytics In Brain Rejuvenationmentioning
confidence: 99%
“…Senolytics are a class of drugs that selectively clear senescent cells through inhibiting their SCAPs, thus driving them into apoptosis. According to their targeted SCAP, first generation senolytics can be subdivided in groups including, i), BCL-2 inhibitors such as navitoclax that inhibit the pro-survival pathway BCL-2/BCL-xL, ii), PI3AK/AKT inhibitors including Dasitinib and Quercetin (D & Q) that constrain the synergistic effects of PI3K and Akt inactivating the apoptosis mediating proteins Bad, caspase-9 and FKHRL1 and iii), FOXO regulators such as Foxo4-DRI interfering with the inhibition of p53mediated apoptosis (52). In addition, cardiac glycosides have been shown to exert senolytics activity through targeting the Na + /K + Atpase (53,54) while most recently a BET family protein degrader targeting the non-homologous end joining and autophagy has been delineated as a promising novel senolytic drug (55) (Table 1).…”
Section: Can Senolytic Drugs Inhibit the Spread Of Senescence?mentioning
confidence: 99%
“…Previous studies have reported that chemotherapy drugs can induce cellular senescence of cancer cells (56)(57)(58)(59). Some claim that some chemotherapy drugs can remove cellular senescence (60,61). Therefore, it is crucial to characterize the senescence status correctly when managing patients with cancer.…”
Section: Effects On the Raf/mek/erk Signaling Pathwaymentioning
confidence: 99%